100 years of women in the dental profession in the UK, 1918-2018 - Brooks, Janine (Cambridge Scholars Publishing, 2019)
This book is a showcase celebration of the achievements of women dental professionals in the 100 years since (some) women first achieved the right to vote in the United Kingdom. Women dentists hold equal status as men within the profession, although there is some way to go before this is mirrored across dentistry as a whole. This volume will serve to provide inspiration to all dental professionals, men and women, regarding the many and varied opportunities dentistry provides. The women profiled are working (or have worked) in all aspects of dentistry, they are role models to all and are a cred.